Analisis Kebutuhan dan Biaya Alat Berat untuk Pekerjaan Pemadatan Lapisan Permukaan Street-Race Circuit Mandalika - Fihani, A.; Hasyim, Hasyim; Karyawan, I.D.M.A. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2021)
The Street-Race Circuit is being built in the Mandalika Tourism Special Economic Zone (KEK), Central Lombok, West Nusa Tenggara. The construction is targeted to be completed, before the MotoGP event on this circuit is implemented in 2021. One of the infrastructure related to this, which also really needs to be built to support the smooth running of the 2021 MotoGP is the development of access to the circuit location. The analysis carried out includes the calculation of heavy equipment productivity. Heavy equipment productivity is determined based on cycle times, production per hour, number of heavy equipment used, the amount of operating costs per hour. The analysis was carried out for the road surface layer work, namely the Asphalt Concrete Base Course (AC-BC) work. Based on the results of the analysis, it was found that the production for 1 unit of asphalt mixing plant (AMP) was 49.80 tons/hour and 9 units of dump trucks were 2.34 tons/hour. The spreader using the asphalt finisher can spread 109.18 tons/hour. As for the compactor, which is 18.55 tons/hour for 2 units of tandem rollers and 27.47 tons/hour for 1 unit of pneumatic tire roller. Other equipment is 9.96 m2/hour for air compressor and 2.74 liter/hour for asphalt sprayer. Meanwhile, in the Asphalt Concrete Wearing Course (AC-WC) work, several tools have the same productivity as the AC-BC job, namely asphalt mixing plant, air compressor and asphalt sprayer. Meanwhile, 13 units of Dump Trucks amounted to 2,338 tons/hour, 1 unit of asphalt finisher of 72,787 tons/hour, 3 units of tandem rollers of 12,367 tons/hour, and 1 unit of pneumatic tire roller of 18.31 tons/hour. The total cost of using heavy equipment for road surface layer work is Rp. 4,967,657,344. The total cost based on the contract document is Rp. 5,042,082,622. So that there is a difference in costs of Rp. 74,425,278.